2006
DOI: 10.1055/s-2005-921173
|View full text |Cite
|
Sign up to set email alerts
|

Early Morbidity of Endoscopic Ultrasound: 13 Years’ Experience at a Referral Center

Abstract: In our experience, which is the longest reported in Europe, the morbidity rates of diagnostic EUS and EUS-guided FNA biopsy were 0.093% and 2.2%, respectively, with no mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
2
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 15 publications
1
40
2
5
Order By: Relevance
“…This is likely due to the small number of cases evaluated with suspected sphincter of Oddi dysfunction for the procedure indication (n = 12). Similar to the ERCP cohort, our overall EUS complication rate was higher than reported in previous studies [17][18][19][20]. This is again likely due to our broad definition of what is considered a procedure-related complication.…”
Section: Discussioncontrasting
confidence: 75%
“…This is likely due to the small number of cases evaluated with suspected sphincter of Oddi dysfunction for the procedure indication (n = 12). Similar to the ERCP cohort, our overall EUS complication rate was higher than reported in previous studies [17][18][19][20]. This is again likely due to our broad definition of what is considered a procedure-related complication.…”
Section: Discussioncontrasting
confidence: 75%
“…For EUS alone, however, there are little data on the safety and utility of propofol sedation [12,17,18,27,36] and comparison of our data to that from other studies is problematic due to variable reported methods, personnel, and monitoring systems utilized for sedation.…”
Section: Splenic Mass (1)mentioning
confidence: 90%
“…L'EE conventionnelle est considérée comme une procédure sûre et avec un taux de complications qui varie de 0,02 à 0,6 %, alors que cette fréquence augmente (0,8-4 %) après biopsie-aspiration guidée par EE [1][2][3][4].…”
Section: Discussionunclassified